Detail analysis of RC parallel network-based model for high capacity lithium ferro phosphates battery - Yao, Low Wen (2012)
RC parallel network-based battery models are popular since they can precisely predict the battery dynamic behaviours including battery relaxation effect. In this paper, the battery model is studied in details. The aim of this paper is to analyse the performances of several RC parallel network-based battery models in high capacity LiFePO4 battery. There are three types of RC parallel network-based battery models used for modelling the high capacity LiFePO4 battery; they are battery model with single RC parallel network, two RC parallel networks and three RC parallel networks. The performances of these RC parallel network-based battery models are discussed in details by comparing the simulated results of the battery models with the experimental data taken from the battery test. In this paper, self-discharging effect, capacity reduction and temperature effect are ignored.